2021
DOI: 10.4314/aas.v18i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Negative Appendectomy Rate in Urban Referral Hospitals in Tanzania: A Cross-sectional Analysis of Associated Factors

Abstract: Background: Acute appendicitis (AA) has a lifetime risk of 8.3% with a consequent 23% lifetime risk of emergency appendectomy. In atypical presentation, making a clinical diagnosis is difficult, leading to a high perforation rate (PR) or misdiagnoses and high negativeappendectomy rates (NAR). This study aimed to establish NAR and explore the associated factors and possible attainable solutions to reduce it in urban referral hospitals in Tanzania. Methods: This was a crosssectional study with 91 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Whether this resulted from attitudes and practices towards AS use for suspected AA could not be determined. However, it has been previously shown that AS is used in only 6% of suspected AA in this setting [ 27 ]. Reasons for its uncommon use need to be determined and addressed to decrease CT overuse and negative appendectomy rates.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this resulted from attitudes and practices towards AS use for suspected AA could not be determined. However, it has been previously shown that AS is used in only 6% of suspected AA in this setting [ 27 ]. Reasons for its uncommon use need to be determined and addressed to decrease CT overuse and negative appendectomy rates.…”
Section: Discussionmentioning
confidence: 99%
“…The reported negative appendectomy rates vary between 11-40% in literature. [12][13][14][15][16][17][18] A rate of 15-20% has been accepted as appropriate to reduce the incidence of perforation in the past but this figure is being challenged these days due to the high post-operative morbidity in patients who have undergone a negative appendectomy. [19][20][21][22][23][24] This diagnostic difficulty has led to the need for developing objective ways of evaluating patients with suspected acute appendicitis by using scoring systems.…”
Section: Introductionmentioning
confidence: 99%